CHARACTER EDUCATION BASED ON RELIGION AND LOCAL WISDOM - I Nyoman Sueca; Ni Wayan Arini; Ni Wayan Satri Adnyani (UHN I Gusti Bagus Sugriwa Denpasar, 2023)
In the current context, character education holds great relevance in addressing the moral crisis affecting Indonesia. This crisis, often overlooked, is alarming and primarily involves the nation's children. It encompasses rising promiscuity, escalating violent behavior among children, student conflicts, plagiarism, drug abuse, and unresolved social issues, among others. Various stakeholders, including policymakers, religious leaders, medical professionals, educators, parents, and the general public, are deeply concerned about this decline in character. Thus, this study aims to investigate the character education conducted in Hindu-based educational institution. This qualitative study took place at Pasraman Gurukula in Bangli Regency, employing purposive sampling to select informants. Data collection methods included observation, interviews, and documentation, with subsequent data analysis involving collection, reduction, presentation, and conclusion-drawing stages. Validation techniques encompassed source triangulation, time triangulation, and technical triangulation. Character education at Pasraman Gurukula is a collaborative effort involving teachers, community leaders, families, and the community, focusing on teamwork, abilities, honesty, and discipline. The education emphasizes religious and local wisdom-based values, fostering cooperation, nationalism, professionalism, integrity, and independence. Teachers play a pivotal role in instilling these values, contributing to the future well-being of children at Pasraman.